Allweiser Schöpfer und durchsetzungsstarker Gesetzgeber: Eine Studie zur erzählerischen Entfaltung des Gottesbildes im 4. Makkabäerbuch - Blumenthal, Christian (Deuterocanonical and Cognate Literature Studies, 2016)
'Reason shall rule over the passions.' In 4 Maccabees, a scripture structured as a praise to God, the anthropocentric focus of this oft-repeated central thesis calls attention to the nature of God's role. This study traces in detail the development of the image of God in 4 Maccabees, and shows that for its author, anthropology is fundamentally rooted in his understanding of God. Christian Blumenthal, Heimbach, Germany.